The (Anti)Social Network: Egocentric Friendship Networks of Incarcerated Youth. Issue 2 (1st February 2017) - Reid, Shannon E.
ABSTRACT: The present study uses egocentric networks collected from youth (aged 14–24) incarcerated with California's Division of Juvenile Justice to examine the composition and structure of youth's friendship networks during periods of incarceration and to test the relationship between friendship and institutional misconduct. Tests of network homophily reveal that youth networks report more diversity across both racial/ethnic categories and gang membership than expected from non-network research about inmate organization. Regression results indicate that youth who stated they had no close friendships within the facility had a lower rate of institutional misconduct post-interview compared to those who nominated peer friendships. The current study demonstrates that incarcerated youth are capable of building close friendships and highlights the potential of these friendships to affect a youth's level of institutional misconduct.